Influence of the Transverse Inhomogeneity on the Nonlinear Post-Buckling Path of Compressed FG Cylindrical Panels - LYKHACHOVA, Olga; KOŁAKOWSKI, Zbigniew (Engineering Transactions, 2017)
In this paper, nonlinear stability of axially compressed cylindrical panels simply supported according to two types of boundary conditions (with possible or limited circumferential displacements of unloaded sides) is presented. Panels made of functionally graded materials (FGMs) of two constituents (metallic and ceramic phases) are treated as multi-layered composite structures with transverse inhomogeneity. Volume fractions of ceramics and metal distribution throughout the layer thickness are described by a simple power law. The influence of the transverse inhomogeneity of FGM panels on unsymmetrical stable post-buckling paths is shown. Special attention is paid to effect of the imperfection sign on post-buckling paths of investigated FGM panels. Some validations of the finite element analysis are discussed for isotropic panels compressed according to two (force and kinematic) loading schemes.